The ubiquitin-proteasome system in neurodegenerative diseases: precipitating factor, yet part of the solution - Dantuma, Nico P.; Bott, Laura C. (Frontiers in Molecular Neuroscience, 2014)
The ubiquitin-proteasome system (UPS) has been implicated in neurodegenerative diseases based on the presence of deposits consisting of ubiquitylated proteins in affected neurons. It has been postulated that aggregation-prone proteins associated with these disorders, such as α-synuclein, β-amyloid peptide, and polyglutamine proteins, compromise UPS function, and delay the degradation of other proteasome substrates. Many of these substrates play important regulatory roles in signaling, cell cycle progression, or apoptosis, and their inadvertent stabilization due to an overloaded and improperly functioning UPS may thus be responsible for cellular demise in neurodegeneration. Over the past decade, numerous studies have addressed the UPS dysfunction hypothesis using various model systems and techniques that differ in their readout and sensitivity. While an inhibitory effect of some disease proteins on the UPS has been demonstrated, increasing evidence attests that the UPS remains operative in many disease models, which opens new possibilities for treatment. In this review, we will discuss the paradigm shift that repositioned the UPS from being a prime suspect in the pathophysiology of neurodegeneration to an attractive therapeutic target that can be harnessed to accelerate the clearance of disease-linked proteins.